Specifications of the ACMG/AMP variant curation guidelines for the analysis of germline CDH1 sequence variants. Issue 11 (11th October 2018) - Lee, Kristy; Krempely, Kate; Roberts, Maegan E.; Anderson, Michael J.; Carneiro, Fatima; Chao, Elizabeth; Dixon, Katherine; Figueiredo, Joana; Ghosh, Rajarshi; Huntsman, David; Kaurah, Pardeep; Kesserwan, Chimene; et al.
Abstract: The variant curation guidelines published in 2015 by the American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG/AMP) provided the genetics community with a framework to assess variant pathogenicity; however, these rules are not gene specific. Germline pathogenic variants in the CDH1 gene cause hereditary diffuse gastric cancer and lobular breast cancer, a clinically challenging cancer predisposition syndrome that often requires a multidisciplinary team of experts to be properly managed. Given this challenge, the Clinical Genome Resource (ClinGen) Hereditary Cancer Domain prioritized the development of the CDH1 variant curation expert panel (VCEP) to develop and implement rules for CDH1 variant classifications. Here, we describe the CDH1 specifications of the ACMG/AMP guidelines, which were developed and validated after a systematic evaluation of variants obtained from a cohort of clinical laboratory data encompassing ∼827, 000 CDH1 sequenced alleles. Comparing previously reported germline variants that were classified using the 2015 ACMG/AMP guidelines to the CDH1 VCEP recommendations resulted in reduced variants of uncertain significance and facilitated resolution of variants with conflicted assertions in ClinVar. The ClinGen CDH1 VCEP recommends the use of these CDH1 ‐specific guidelines for the assessment and classification of variants identified in this clinically actionable gene. Abstract : Germline pathogenic variants in the CDH1 gene cause hereditary diffuse gastric cancer and lobular breast cancer. The ClinGen CDH1 Expert Panel developed and implemented rules for CDH1 variant curation, providing the genetic community with a gene‐specific framework for the classification of variants identified in this clinically actionable gene. Overall, the Expert Panel specifications resulted in reduced variants of uncertain significance and facilitated resolution of variants with conflicted assertions in ClinVar.